Odpowiedź :
Odpowiedź:
B) - 6x+8=4 | - 8
-6x=-4 |: (-6)
X= 4/6=2/3
C) 5x-14=6 |+14
5x=20 |:5
X=4
D) 9-x=24 |-9
-x=15. |*(-1)
X=-15
E) 5+4x=29 |-5
4x=24 |:4
X=6
F)1/5x-2=4 |* 5
X-10=20 |+10
X=30
Odpowiedź:
b) -6x+8=4 /-8
-6x+8-8=4-8
-6x=-4 / *-1
-6x*-1= -4*-1
6x=4 / :6
6x:6=4:6
X= 0,6666666666666
c)
5x-14=6 /+14
5x-14+14= 6+14
5x= 20 /:5
5x:5=20:5
X= 4
d)
9-x=24 /-9
9-x-9= 24-9
-x= 15 /*-1
-x*-1= 15*-1
X= -15
e)
5+4x=29 /-5
5+4x -5= 29-5
4x= 24 /:4
4x:4= 24:4
X= 6
f)
⅕x-2=4 / *5
⅕x*5-2*5=4*5
X-10=20 /+10
X-10 +10= 20 +10
X= 30
Mam nadzieje że pomogłam